Drought Effects on Tectona grandis Water Regulation Are Mediated by Thinning, but the Effects of Thinning Are Temporary - Sinacore, Katherine; Breton, Connor; Asbjornsen, Heidi; Hernandez-Santana, Virginia; Hall, Jefferson S. (Frontiers in Forests and Global Change, 2019)
Results from tropical planted forests have demonstrated that tree plantations can have variable growth and water use patterns in response to drought. Yet research on how specific species will perform during a drought and whether this response can be mediated through forest management is still poorly understood. We took advantage of the 2015-2016 El Niño drought in central Panama to test the effects of thinning on sap flux density, transpiration, and growth of planted Tectona grandis (teak), a non-native species introduced to Panama for timber production. Despite a reduction in growth of teak during drought for control and thinned sites, tree sap flux density of thinned sites significantly temporarily increased after the thinning. Sap flux density (Js) for teak is strongly driven by changes in vapor pressure deficit (VPD), temperature, and radiation; however, Js declines as temperature rises above 28C and VPD is above 0.5, suggesting a temperature threshold that could be problematic as droughts and temperatures increase in unison in the future. At the stand-level, all sites reduced transpiration during the drought. Although diameter growth and transpiration declined during drought, the leaf area index after the drought ended returned to pre-drought levels.